Dysbiosis of the Salivary Microbiome Is Associated With Non-smoking Female Lung Cancer and Correlated With Immunocytochemistry Markers - Yang, Junjie; Mu, Xiaofeng; Wang, Ye; Zhu, Dequan; Zhang, Jiaming; Liang, Cheng; Chen, Bin; Wang, Jingwen; Zhao, Changying; Zuo, Zhiwen; Heng, Xueyuan; Zhang, Chunling; et al. (Frontiers in Oncology, 2018)
Background: The associations between oral bacteria and increased risk of lung cancer have been reported in several previous studies, however, the potential associations between salivary microbiome with non-smoking female lung cancer have not been evaluated. There is also no report on the relationship between immunocytochemistry markers and salivary microbiota. Method: In this study, we assessed the salivary microbiome from 75 non-smoking female lung cancer patients and 172 matched healthy individuals using 16S rRNA gene amplicon sequencing. We also calculated the Spearman's rank correlation coefficient between salivary microbiota and three immunohistochemical markers (TIF-1, Napsin A and CK7) Result: We analyzed the salivary microbiota of 247 subjects and found that non-smoking female lung cancer patients exhibited oral microbial dysbiosis. Significantly lower microbial diversity and richness were found in lung cancer patients when compared to the control group (Shannon index, P < 0.005; Ace index, P < 0.0001). Based on the analysis of similarities, the composition of the microbiota in lung cancer patients was also different from that of the control group (r = 0.454, P < 0.005, unweighted UniFrac; r = 0.113, P < 0.005, weighted UniFrac). The relative abundance of the bacterial genera Sphingomonas (P < 0.0001) and Blastomonas (P < 0.0001) were enriched in non-smoking female lung cancer patients, whereas Acinetobacter (P < 0.0001) and Streptococcus (P < 0.0001) were enriched in controls. Based on the Spearman correlation analysis, a significantly positive correlation can be observed between CK7 and Enterobacteriaceae (r = 0.223, P < 0.05). Meanwhile, Napsin A was positively associated with genera Blastomonas (r = 0.251, P < 0.005). TTF-1 exhibited a significantly positive correlation with Enterobacteriaceae (r = 0.262, P < 0.05). Functional analysis from inferred metagenomes indicated that oral microbiome in non-smoking female lung cancer were related to pathways in cancer, p53 signaling pathway, apoptosis and tuberculosis. Conclusions: Our study identified distinct salivary microbiome profiles in non-smoking female lung cancer, revealed potential correlations of salivary microbiome with immunocytochemistry markers used in clinical diagnostics, and provided proof of salivary microbiota as an informative source for discovering non-invasive biomarkers of lung cancer.